The Experiences of Witnesses to Prison Sexual Violence: A Case Study - Hendricks, Edyth Zada (2019)
Prison sexual violence is prevalent and impacts the witnesses to it. Previous literature has fully discussed the victims of prison sexual violence; however there remains an important gap in the current literature regarding the experiences of witnesses. The purpose of the present qualitative case study was to explore the lived experiences of witnesses to prison sexual violence. The theoretical foundation of this study was the self-categorization theory linked to the prison code of silence. Four ex-inmates answered semi structured interview questions. Transcripts were coded and themes developed. Five themes that emerged were exposure (to prison sexual violence), ineffective guards, avoidance (of witnessing prison sexual violence), distress, and violence. The themes of this study add more information to the literature regarding witnessing prison sexual violence by expanding information beyond aggression and violence. Recommendations from this research can assist prison administrators with assisting to break the prison code of silence; which would enhance social change